2012
DOI: 10.1149/2.019203jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Ascorbic Acid at Copper Germanate Nanowire Modified Electrode

Abstract: Copper germanate (CuGeO 3 ) nanowires are used as the modified materials of glassy carbon electrode to investigate the electrochemical behavior of ascorbic acid. The results show that CuGeO 3 nanowire modified glassy carbon electrode exhibits good performance for the electrochemical detection of ascorbic acid in neutral solution. The intensities of two anodic peaks vary linearly with the concentration of ascorbic acid in the range of 0.01-5 mM and the detection limit is 24 μM and 8.6 μM, respectively at a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…22,23 In our past research, crystalline calcium germanate nanowires, 24,25 cadmium germanate nanowires 26 and copper germanate nanowires 27 have been synthesized via a simple hydrothermal process by adjusting the metal and salt acetate raw materials and they exhibited good optical and electrochemical properties. 28,29 In this paper, single crystalline Sr germanate nanowires with the orthorhombic SrGeO 3 phase have been synthesized via a simple hydrothermal process using Ge dioxide and Sr acetate as the raw materials. The structure, morphology, size and optical properties of the Sr germanate nanowires have been analyzed by X-ray diffraction (XRD), electron microscopy (EM), Fourier transform infrared (FTIR) and ultraviolet-visible (UV-vis) diffusion reflectance spectra.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 In our past research, crystalline calcium germanate nanowires, 24,25 cadmium germanate nanowires 26 and copper germanate nanowires 27 have been synthesized via a simple hydrothermal process by adjusting the metal and salt acetate raw materials and they exhibited good optical and electrochemical properties. 28,29 In this paper, single crystalline Sr germanate nanowires with the orthorhombic SrGeO 3 phase have been synthesized via a simple hydrothermal process using Ge dioxide and Sr acetate as the raw materials. The structure, morphology, size and optical properties of the Sr germanate nanowires have been analyzed by X-ray diffraction (XRD), electron microscopy (EM), Fourier transform infrared (FTIR) and ultraviolet-visible (UV-vis) diffusion reflectance spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al [24] reported two anodic CV peaks from the CV curves at the copper vanadate nanobelts modified GCE in 0.1 M KCl solution with 2 mM ascorbic acid appeared at the potential of 0.12 and 0.02 V, respectively. Two pairs of semi-reversible CV peaks were also observed from the CV curves at CuGeO 3 nanowire modified GCE in 0.1 M KCl solution with 2 mM ascorbic acid [25]. The anodic CV peaks appeared at 0.20 and 0.02 V, respectively.…”
Section: Electrochemical Responses Of Bamentioning
confidence: 81%
“…Two pairs of semi-reversible CV peaks were also observed from the CV curve of ascorbic acid at the ternary copper germanate nanowire modied GCE. 35 Two anodic CV peaks (cvp1, cvp2) were located at +0.20 V and +0.02 V and two cathodic CV peaks (cvp1 0 , cvp2 0 ) were located at +0.07 V and À0.41 V, respectively. The electrochemical CV peaks at the copper germanate nanowire modied GCE were assigned to the oxidation-reduction process (cvp1-cvp1 0 ) and adsorptiondesorption process (cvp2-cvp2 0 ) between ascorbic and dehydroascorbic acid, respectively.…”
Section: Resultsmentioning
confidence: 96%